The Implementation of Edushell's Learning Media to Improve Vocabulary in Learning English in Grade 3 MI Al-Fath Asem Manis Ngawen Sidayu - Barianty, Trishna Nanda; Maqfirah, Dinita Dewi; Supit, Hesti Diana; Irawan, Deni (Kontribusia : Research Dissemination for Community Development, 2019)
This study aims to improve the quality of learning English using the media of clamshell waste in Asem Manis Hamlet, Ngawen Village, sub-district Sidayu, Gresik.Classroom learning must be done optimally, but the teaching staff still cannot be maximally applied, if this can be maximized, then this can improve the quality of educational products that have outcomings for stakeholders. Because of its relevance, it is essential for the teacher to make breakthroughs in learning, one of which is the creativity of the teacher to make learning media by using waste that is around the environment. Participants were grade 3 students of MI Al-Fath, totaling 11 people. This research method uses the instrument pre-test, and post-test conducted to retrieve data. Then using the learning by doing method that is applied in the classroom, students not only listen to the teacher speak but also practice it in the classroom. Although it looks, shy students can do these activities well The results show that participants were happy to use Edushell's media in their learning. The results of the research given by the authors are the application of the media can improve the English language skills of students and be able to provide variations in indoor learning that are not only fixed on the Package Books and Student Worksheets (LKS). Not only that, but the writer also found that the media was able to change the mood of students doing teaching through the media